2000
DOI: 10.1046/j.1365-2222.2000.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin treatment of chronic idiopathic urticaria and angio‐oedema

Abstract: This is the first double-blind placebo-controlled study to show a response of chronic idiopathic urticaria to warfarin. The mechanisms of action are unclear and require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 11 publications
0
48
0
1
Order By: Relevance
“…However, the fact that such an activation parallels the activity of CU may provide the rationale for an anticoagulant and antifibrinolytic therapy in patients with severe CU. The effectiveness of anticoagulant therapy in some patients with refractory CU was observed more than a decade ago (90) by the use of oral anticoagulants and more recently by the use of heparin (14,91,92). The use of heparin can be effective in patients with urticaria who have high levels of D-dimer and poor response to antihistamines (14,85).…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that such an activation parallels the activity of CU may provide the rationale for an anticoagulant and antifibrinolytic therapy in patients with severe CU. The effectiveness of anticoagulant therapy in some patients with refractory CU was observed more than a decade ago (90) by the use of oral anticoagulants and more recently by the use of heparin (14,91,92). The use of heparin can be effective in patients with urticaria who have high levels of D-dimer and poor response to antihistamines (14,85).…”
Section: Discussionmentioning
confidence: 99%
“…In effect, there have already been scattered reports, and 1 double-blind placebo-controlled study as well, suggesting that anticoagulants (either heparin or warfarin) may be effective in the treatment of CU [19,20,21,22,23], although the efficacy of warfarin has not been confirmed by other authors [24], possibly due to the heterogeneity of the pathomechanisms involved in this disease. Further, we and others have previously shown that heparin is able to turn a markedly positive intradermal autologous serum skin test negative [25,26], and that heparin inhibits the histamine release activity of sera from CU patients on cultured basophils [26].…”
Section: Discussionmentioning
confidence: 99%
“…A small double-blind, placebo-controlled study carried out about 15 years ago first detected the effectiveness of oral anticoagulant therapy in some patients with refractory CSU [48]. After an attempt carried out more than 60 years ago [49], in some more recent studies, heparin also has been effective in patients with severe disease [50,51] and elevated D-dimer plasma levels [52].…”
Section: Anticoagulants/antifibrinolytics In Chronic Spontaneous Urtimentioning
confidence: 99%